A New Ni(II) Coordination Polymer Based on Imidazole-Containing and Dicarboxylate Ligands with Polycatenated 2D + 2D → 3D Framework. Issue 8 (2nd August 2016) - Yang, Lili
Abstract : A new coordination polymer, [Ni(sdb)(bimb)1.5 ]·H2 O (1 ) (H2 sdb = 4, 4'-sulfonyl- dicarboxylic acid and bimb = 1, 4-bis(1-imidazol-yl)-2, 5-dimethyl benzene) has been prepared by hydrothermal synthesis and characterized by elemental analysis, IR, and X-ray diffraction. Complex [Ni(sdb)(bimb)1.5 ]·H2 O (1 ), monoclinic, space group P 21 /c with a = 13.494(5)Å, b = 14.313(5) Å, c = 17.803(5) Å, β = 97.792(5)°, V = 3407(2) Å 3, Z = 4, Mr = 738.43, Dc = 1.440 g/cm 3, F (000) = 1532, and µ = 0.689 mm −1 . The final refinement gave R = 0.0351and wR = 0.0950 for 6688 reflections with I > 2σ( I ). X-ray diffraction analysis reveals that complex1 shows a three-dimensional 2D + 2D → 3D Framework.